Evaluación de la enseñanaza del aragonés en centros públicos de Educación Infantil y Primaria - Campos, I.O. (2018)
Although it is the 20 years since Aragonese language was introduced in some schools of Huesca’s province, there is still little scientific data about the situation and prospects of this language in the educational area. With the aim of providing evidence about this issue, we developed an exploratory research under a mixed methodology, and focused on the attitudes towards Aragonese language of Primary Education students in Huesca province and the communicative competence of those children who are learning Aragonese. In this paper we analyse the data refering to the communicative competence of children that are learning Aragonese. These data were obtained under a double method (qualitative and quantitative). Results show the insufficient competence achieved by those children who don’t have Aragonese as their L1/L2, in terms of grammar and expressive skills.